2018
DOI: 10.3390/nano8070482
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polymer Microstructure on Encapsulation Efficiency and Release Kinetics of Citropin 1.1 from the Poly(ε-caprolactone) Microparticles

Abstract: Cationic antimicrobial peptides represent a promising therapeutic option against multidrug-resistant bacteria for the treatment of local infections. However, due to their low stability and potential toxicity, there are limited possibilities for their application in clinical practice. In this study, different poly(ε-caprolactone) (PCL) microparticles (MPs) loaded with citropin 1.1 (CIT) were investigated in order to demonstrate the effect of the polymer microstructure on the encapsulation efficiency (EE) and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Due to this fact, significant efforts and different strategies have been engaged in the past decades to protect AMPs from degradation, inactivation and to improve their biocompatibility including by substitution with unnatural amino acids, d -amino acids, W or end-caps, varying chain length, cyclization or polymerization [4345]. Another approach to increasing clinical use is through increasing stability and by decreasing their toxicity through the use of drug carriers [46]. Our previous studies have shown that both physical and covalent immobilization on the nanoparticle surface markedly enhances the activity of AMPs and their chemical analogs [23, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this fact, significant efforts and different strategies have been engaged in the past decades to protect AMPs from degradation, inactivation and to improve their biocompatibility including by substitution with unnatural amino acids, d -amino acids, W or end-caps, varying chain length, cyclization or polymerization [4345]. Another approach to increasing clinical use is through increasing stability and by decreasing their toxicity through the use of drug carriers [46]. Our previous studies have shown that both physical and covalent immobilization on the nanoparticle surface markedly enhances the activity of AMPs and their chemical analogs [23, 47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many polymeric nanoparticles are bio-degradable and cleared through metabolic pathways in the bodies ( Chan et al, 2010 ). Moreover, to facilitate the local administration and the release rate, the polymeric nanoparticles that are conjugated with peptides have been shown to demonstrate near-first-order or near-zero distribution without burst release; as a result, it has emerged as a promising system of drug delivery to treat local infections ( Piotrowska et al, 2018 ). This was further exemplified by the application of multi-polymers, such as a combined use of chitosan and polyethylene glycol, a procedure that has been shown to decrease the propensity to aggregate and make the nanoparticles more stable and biocompatible ( Calvo et al, 1997 ).…”
Section: Incorporation Of Amps Into Nanoparticles and Polymersmentioning
confidence: 99%
“…46 For instance, Grillo and colleagues developed PCL nanopesticides containing atrazine and obtained a release exponent (n) of 0.92, indicating that the system is also controlled by non-Fickian diffusion. 21 Other PCL microparticles with different active ingredients (e.g., cationic antimicrobial peptides, 48 nonsteroidal anti-inflammatory drug, 49 antihypertensive therapy 50 ) have shown a similar diffusion process.…”
Section: Determination Of Herbicide Encapsulationmentioning
confidence: 99%